Konsep Pendidikan Kesehatan Mental Dalam Mengatasi Problematika Kehidupan Perspektif Al-Qur’an - Maghfiroh, Ni’matul; Faradhita, Rowiena; Budiyanti, Firda Putri (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Mental health problems are often experienced by teenagers, especially those who are currently studying. This is evidenced by the many viral news about suicide cases that occur almost every month. Those who commit suicide feel that by committing suicide their problems will be solved by following their lives. The purpose of this article is to provide an overview to readers, about how to overcome problems related to mental health education according to the Qur'an. The research method that I use is library research with a historical, critical, and philosophical approach and descriptive analysis. The results obtained are that the concept of mental health education according to the Qur'an has been explained and we have even done it without realizing the benefits behind it. According to the Qur'an, there are six concepts that can be applied in everyday life. the first is the first in QS. Ali Imran verse 110 about ordering to do good and forbidding to do bad, the second in QS. Al Baqarah verse 155 about applying patience in facing tests, the third in QS. Adz-Zariyat verse 56 about carrying out worship to Allah, the fourth in QS. Al-Insyirah verse 6 about every difficulty there must be ease, fifth in QS. Al-Ra'ad verse 28 about always making dhikr to remember Allah, and sixth in QS Ibrahim verse 7 about always being grateful. With several concepts that are strengthened by verses from the Qur’an, we can apply them in everyday life. So that we can apply and help if one day someone experiences mental problems.